2021
DOI: 10.1177/03000605211056834
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged corrected QT interval in hospitalized patients with coronavirus disease 2019 in Dubai, United Arab Emirates: a single-center, retrospective study

Abstract: Objective To evaluate the association of a prolonged corrected QT (QTc) interval in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and its association with in-patient mortality. Methods A cohort of 745 patients were recruited from a single center between 1 March 2020 and 31 May 2020. We analyzed the factors associated with a prolonged QTc and mortality. Results A prolonged QTc interval >450 ms was found in 27% of patients admitted with SARS-CoV-2 infection. These patients were predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…QT prolongation (42.0%) in COVID-19 was found to be 4.48 times a significantly higher risk of death than normal QT interval. This finding was supported by a previous retrospective study in Dubai, which stated that a QTc interval >450 ms was significantly associated with ventilation requirements and increased mortality [15]. A study by Fishbein et al found that delayed cardiac repolarization as indicated by QTc > 500 ms was an independent predictor of mortality in COVID-19 patients (OR= 1.41; 95% CI= 1.05-1.90) [16].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…QT prolongation (42.0%) in COVID-19 was found to be 4.48 times a significantly higher risk of death than normal QT interval. This finding was supported by a previous retrospective study in Dubai, which stated that a QTc interval >450 ms was significantly associated with ventilation requirements and increased mortality [15]. A study by Fishbein et al found that delayed cardiac repolarization as indicated by QTc > 500 ms was an independent predictor of mortality in COVID-19 patients (OR= 1.41; 95% CI= 1.05-1.90) [16].…”
Section: Discussionmentioning
confidence: 58%
“…The QT interval on the ECG is one of the indicators in the clinical evaluation of patients at high risk of experiencing ventricular arrhythmias and myocardial infarction, which is characterized by increased cardiac biomarkers of troponin and BNP [15]. QT prolongation (42.0%) in COVID-19 was found to be 4.48 times a significantly higher risk of death than normal QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 infection is also associated with myocardial injury, indicated by both elevated cardiac biomarkers [Troponin and brain natriuretic peptide (BNP)] ( 12 15 ) and echocardiographic abnormalities ( 16 ). Previous studies described the association of QTc prolongation to myocardial injury and to short term mortality ( 17 19 ), and in the largest cohort consisting of 7,098 hospitalized COVID-19 patient, Fishbein et al ( 20 ) reported that extremely prolonged QTc (>500 ms) was an independent predictor for in-hospital mortality. However, the association of prolonged QTc to long term mortality, had not yet been described.…”
Section: Introductionmentioning
confidence: 99%